Genetic analysis and QTL mapping of early root bulking in an F1 population of non-inbred parents in cassava (Manihot esculenta Crantz) - Okogbenin, Emmanuel; Fregene, Martin A. (Springer, 2002)
The genetic basis of early bulking in cassava was studied in a replicated, multi-locational trial using 144 F1 progeny derived from an intra-specific cross between two non-inbred parents. A second, sequential harvest experiment examined the relative importance of eight yield-related traits on early bulking and their QTLs during the crop growth cycle. Our objectives were to identify traits, and genes controlling them, strongly associated with early yield as a first step to marker-assisted improvement of the trait. Multiple linear regression analysis and stepwise regression of early yield on eight yield-related traits revealed harvest index, dry foliage weight and root diameter as the most important factors associated with early yield. A total of 18 QTLs controlling early yield were identified in the first and second experiments and 27 QTLs, 2 for dry foliage weight, 8 for harvest index and 17 for root diameter, in the second experiment. The individual effects of alleles at these QTLs identified ranged from 7% to 33% of the phenotypic variance explained. Seven of 18 QTLs found for early yield (39%) coincided with QTLs associated with one or more traits with significant influence on early yield. The results show that sink and source capacities are very important in determining early yield. The identification of a number of QTLs with positive effect for increased early yield provides an opportunity for marker-assisted selection and improvement of early bulking potential in cassava.